ANALISIS PENGARUH CURRENT RATIO (CR), TOTAL ASSET TURN OVER (TATO), RETURN ON EQUITY (ROE) TERHADAP PERUBAHAN LABA PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B11110037, Yosanti Martaria T (Jurnal Manajemen Update, 2014)
Food and beverage sub-sector is one of the sub-sectors in the manufacturing industry plays an important role in the development of the industrial sector, especially the value of PDB, and the annual company food and beverage sub-sector earnings changes either increase or decrease. Therefore, this study focused on the factors that influence changes in food and beverage sub-sector earnings are listed on the Stock Exchange with the financial statements for the period 2008-2012. The number of samples in this study were 12 companies. The method of analysis used is multiple linear regression models with SPSS. Factors thought to affect change in earnings in this study is the Current Ratio (CR), Total Asset Turn Over (TATO), and Return on Equity (ROE). The results of this study showed CR, TATO, and ROE jointly have a significant influence on the changes in food and beverage profits. While the partial CR and TATO not significant effect on changes in earnings, while the ROE has a significant positive effect on earnings changes. Conclusion This study menunujukkan predictor variables that can be the change in profit is ROE while CR and TATO can not be used as a predictor because it was not associated with changes in food and beverage profits. Â  Keywords: Changes in Earnings, Current Ratio, Total Asset Turn Over, Return on Equity